APPLYING VISUAL THINKING STRATEGY TO MATERNAL/WOMEN’S HEALTH NURSING: A QUASI-EXPERIMENTAL STUDY - Isroilova, N.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The visual thinking strategy is a set of methods and techniques that help to visualize a person’s thoughts, emotions, and ideas. This strategy is widely used in educational settings as well as in healthcare and caregiving. Its significance is particularly notable in the care of maternal and women’s health. This article focuses on the role of visual thinking strategies in maternal and women’s health care and presents the results of a quasi-experimental study aimed at evaluating their effectiveness.